La alquimia democrática. Ciudadanos y procedimientos representativos en Bolivia (1825-1879) - Irurozqui, Marta (2008)
This article studies the expressions and the institutionalization of popular sovereignty in post-independent Bolivia (1825-1879) by analyzing two components of the democratic system: the subjects involved and the procedures for representation. As far as the former, the article underlines the fact that being a citizen was not limited to voting, but was also exercised by other activities connnected with work, taxation, public petitions and the use of arms. On the other hand, the study of the procedures for organizing and the carrying out of elections highlights two additional realities: first, voting had a regulatory function intended to level off competition and avoid conflicts, and secondly, the reduced number of the electoral body did not inhibit the development of political competition because political participation went beyond elections to include the use of violence and other illegal activities